Antioxidant properties: effects of solid-to-solvent ratio on antioxidant compounds and capacities of pegaga (Centella asiatica) - Tan, P. W.; Tan, Chin Ping; Ho, Chun Wai (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2011)
The objective of this study was to evaluate the effects of solid-to-solvent ratio (1:5, 1:10, 1:15 and 1:20) on the extraction of phenolic compounds (TPC and TFC) and antioxidant capacity (ABTS and DPPH radical scavenging capacity) of C. asiatica. Solid-to-solvent ratio 1:15 was the optimum condition for extraction of phenolic compounds (TPC and TFC) with a value of 967.2 mg GAE/100 g DW and 908.3 mg CE/100 g DW, respectively and exhibited high antioxidant capacities (ABTS and DPPH radical scavenging capacities) with a value of 0.8133 mM and 2.0945 mM, respectively. TPC was positively and strongly correlated with ABTS and DPPH (r=0.808 and r=0.859, respectively) under the effects of solid-to-solvent ratio as compared to TFC, positively and moderately correlated (r=0.590, r=0.663) with ABTS and DPPH.